Monolithic Integrated Schottky Diode Multiplier and Rectenna for Wireless Communication Link in the W Band - Alina C. Bunea; Dan Neculoiu; Antonios Stavrinidis; George Stavrinidis; Athanasios Kostopoulos; George Konstantinidis (IEEE Access, 2022)
A W band (75 – 110 GHz) communication link using monolithic integrated single-diode circuits is proposed. The circuits are based on GaAs Schottky diodes with cutoff frequencies around 1.5 THz integrated with on chip folded slot antennas and near-field 3D printed dielectric lenses. The total chip area is $1.4×3.5$ mm2. The receiver module shows a peak isotropic voltage sensitivity of 12260 mV/mW at 94 GHz, with a noise equivalent power of 12 pW/ $\sqrt {Hz} $ . These results include the slot antenna and a 3 mm radius 3D printed lens. The transmitter acts as a free-space W band signal generator using the non-linear properties of the diode for frequency multiplication. Multiplication orders up to $× 15$ are tested for input powers of 10 mW. The generated power is measured by a horn antenna placed at a distance of 100 mm from the transmitter and a 2D map for the frequency range 90 – 100 GHz and multiplication orders between $× 2… × 15$ is presented. The two circuits are used to demonstrate W band communication links using 1 kHz amplitude modulated input signals with carriers at 6 GHz, X band and in the Ku band. Voltages of hundreds of mV are detected for a distance of 150 mm between transmitter and receiver circuits and tens of mV at 600 mm. The proposed approach can be used as a low cost and low complexity alternative for point-to-point high-speed wireless communications.